PENGARUH PENGEMBANGAN KARIER, PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. PLN (Persero) UP3 Surakarta - Claudya Mayasaputri Kumalasari; Suprayitno Suprayitno; Lamidi Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study was to analyze the significance of the influence of career development, training and work discipline on employee performance. This type of research is a census of the employees of PT. PLN (Persero) UP3 Surakarta. This type of data uses qualitative and quantitative data. Data sources used are primary data and secondary data. The study population was all employees of PT. PLN (Persero) UP3 Surakarta as many as 40 people. In this study because the population is less than 100, the sampling technique is total sampling, which is the technique of determining the sample if all members of the population are used as a sample (census). Data collection techniques using questionnaires, documentation and observation. This study uses a Multiple Linear Regression Analysis tool then it must use the Classic Assumption Test consisting of Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test and Normality Test, then the data analysis technique used is Descriptive Analysis and Inductive Analysis consisting of Multiple Linear Regression Analysis, Partial Influence (t Test), Simultaneous Influence Test (F Test) and Determination Coefficient Test (R2 ). The results of this study indicate that career development has a significant effect on employee performance. Training has a significant effect on employee performance. Work discipline has a significant effect on employee performance.